Workshop Penyusunan Evaluasi Pembelajaran menggunakan Artificial Intelligence (AI) di SMK Kesehatan Pelita Bangsa - Kusumaningrum, Betty; Wijayanto, Zainnur; Pardimin, Pardimin; Riyanita Sarani, Fajar; Azis Muhaimin, Nur; Salma Azizah, Salma (Journal of Community Capacity Empowerment, 2025)
The use of artificial intelligence (AI) technology has resulted in fundamental changes in various aspects of human life, including in the field of education. However, the ability to utilize AI technology has not been widely mastered by teachers and educators. The workshop "Learning Evaluation Using Artificial Intelligence (AI)" at SMK Kesehatan Pelita Bangsa aims to improve teacher skills in using AI for learning evaluation. This workshop answers the need for more effective, efficient, and objective evaluation methods in modern education. This activity was attended by 25 SMK Kesehatan Pelita Bangsa teachers. This community service activity was carried out through 3 stages, namely socialization, workshops, and mentoring. This activity received positive feedback where 87% of teachers considered the material presented relevant, 88% appreciated the clarity of the presentation, and 86% felt the time given was sufficient. In addition, 89% felt the workshop was useful, 90% felt the material was easy to understand, and 80% agreed to apply what they learned. These results indicate that this workshop has succeeded in achieving its objectives and has had a positive impact on the quality of learning evaluation in schools. Teachers gain new knowledge and are motivated to apply it in their teaching. The use of AI in evaluation is expected to provide more meaningful and accurate feedback, so that it can support improving the overall quality of education.